Low-temperature synthesis of carbon nanotubes via floating catalyst chemical vapor deposition method - Rashid, A. Mahmood; Awang Biak, Dayang Radiah; Zainal Abidin, Zurina; Ahmadun, Fakhru'l-Razi (Taylor & Francis, 2011)
Carbon nanotubes (CNTs) are widely synthesized at high temperatures via floating catalyst chemical vapor deposition (FC-CVD) method. It is important to reduce the synthesis temperature of CNTs to allow better control of the reactor's conditions and to eliminate the formation of carbon by-products. The main objective of this work was to synthesize carbon nanotubes at low temperatures. Temperature in-situ monitoring unit was used to monitor the temperature profile in the reactor. Benzene and ferrocene were used as the carbon source and catalyst precursor, respectively. The minimum pyrolysis temperature of benzene was successfully estimated, and the investigation of temperature profile in the reactor was achieved. In this work, multi-walled CNTs were successfully synthesized for synthesis temperatures between 540°C and 600°C. Based on the analyses, the qualities of CNTs produced were profoundly improved with the increase of synthesis temperatures.